Comparative efficacy of ancillary drugs in sevoflurane‐related emergence agitation after paediatric adenotonsillectomy: A Bayesian network meta‐analysis. (7th April 2020) - Jiao, Hongmei; Wang, Hongwei; Jiang, Ziru; Hu, Jingli
Abstract: What is known and objective: The comparative efficacy of ancillary drugs on sevoflurane‐related emergence agitation (EA) in paediatric anaesthesia for adenotonsillectomy remains unclear. The purpose of this Bayesian network meta‐analysis was to investigate the efficacy of ancillary drugs on sevoflurane‐related EA in paediatric anaesthesia for adenotonsillectomy. Methods: MEDLINE, Embase, the Cochrane Library and Web of Science databases were electronically searched to identify randomized controlled trials (RCTs) of different ancillary drugs used in adenotonsillectomy from inception to April 2019. Two reviewers independently screened the literature, extracted data and assessed the risk of bias in included studies. Subsequently, a network meta‐analysis was performed using the R software and RevMan 5.3 software. Results and discussion: We included 25 RCTs, involving 2151 participants. The proportion of patients with sevoflurane‐related EA was significantly lower in the dexmedetomidine, ketamine, propofol, fentanyl, midazolam, sufentanil, remifentanil and clonidine groups than in the placebo group ( P < .05). Fentanyl was superior to sufentanil ( P < .05), whereas dexmedetomidine was superior to fentanyl ( P < .05). Among ancillary drugs, dexmedetomidine (90.04%) showed the highest possibility of reducing the risk of EA, followed by fentanyl (87.45%), remifentanil (63.85%), ketamine (52.07%), midazolam (51.27%), clonidine (49.94%), propofol (29.89%), sufentanil (21.38%) and placebo (4.09%). What is new and conclusion: Evidence suggests that the effects of dexmedetomidine in reducing the risk of sevoflurane‐related EA in paediatric anaesthesia for adenotonsillectomy were better than the effects of other drugs. However, large, high‐quality RCTs are required to further confirm this. Abstract : The results of the present network meta‐analysis showed that the risk of sevoflurane‐related EA was lower in the dexmedetomidine, ketamine, propofol, fentanyl, midazolam, sufentanil, remifentanil and clonidine groups than in the placebo group. The effects of dexmedetomidine in reducing the risk of sevoflurane‐related EA in paediatric anaesthesia for adenotonsillectomy were better than the effects of other drugs.